Role of Arabidopsis Splicing factor SF1 in Temperature-Responsive Alternative Splicing of FLM pre-mRNA - Lee, Keh Chien; Chung, Kyung Sook; Lee, Hee Tae; Park, Jae-Hyeok; Lee, Jeong Hwan; Kim, Jeong-Kook (Frontiers in Plant Science, 2020)
Small changes in temperature affect plant ecological and physiological factors that impact agricultural production. Hence, understanding how temperature affects flowering is crucial for decreasing the effects of climate change on crop yields. Recent reports have shown that FLM-, the major spliced isoform of FLOWERING LOCUS M (FLM)—a flowering time gene, contributes to temperature-responsive flowering in Arabidopsis thaliana. However, the molecular mechanism linking pre-mRNA processing and temperature-responsive flowering is not well understood. Genetic and molecular analyses identified the role of an Arabidopsis splicing factor SF1 homologue, AtSF1, in regulating temperature-responsive flowering. The loss-of-function AtSF1 mutant shows temperature insensitivity at different temperatures and very low levels of FLM- transcript, but a significantly increased transcript level of the alternative splicing (AS) isoform, FLM-. An RNA immunoprecipitation (RIP) assay revealed that AtSF1 is responsible for ambient temperature-dependent AS of FLM pre-mRNA, resulting in the temperature-dependent production of functional FLM- transcripts. Moreover, alterations in other splicing factors such as ABA HYPERSENSITIVE1/CBP80 (ABH1/CBP80) and STABILIZED1 (STA1) did not impact the FLM-/FLM- ratio at different temperatures. Taken together, our data suggest that temperature-dependent interaction between AtSF1 and FLM pre-mRNA controls flowering time in response to temperature fluctuations.